Pendampingan EMKM Huma Cake Melalui Pembuatan Banner Usaha, Re-Packaging Kemasan, Pembuatan Laporan Keuangan Usaha dan Pembaharuan Visual Tempat Usaha Pada Google Maps - Marbun, Melia Rumata; Sella, Nivada Two; Santaria, Nola; Fajriati, Nur Anida; Hasanah, Nur (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to provide comprehensive support services, including branding, financial management training, and digital marketing guidance at Huma Cake. The community service activity was carried out on August 25-September 27, 2024 in the form of mentoring and training including the preliminary activity stage, implementation stage and evaluation stage. The results of the mentoring activity showed a significant increase in branding, financial management, and the bakery's digital presence. Customized banners increased the bakery's visibility, while redesigned packaging increased product appeal. Financial management training equipped business owners with the skills to track income and expenses more effectively.